52 SUB-CLINICAL IMFLAMMATION CONTRIBUTES TO THE EARLY DEVELOPMENT OF CARDIOVASCULAR DISEASE IN THE NON-HYPERENSIVE YOUNG HEALTHY PREFESSIONALS. (1st January 2005) - Zhang, R.; Butterbaugh, G.; Liao, J.; Aguilar, E.; Rose, M.; Roques, B.; Thomson, J.; Elmore, K.; Reisin, E.
Abstract : Introduction: Many demographic and metabolic factors contribute to cardiovascular disease (CVD). Recently, systemic inflammation was proposed to be a new risk factor for CVD. The common carotid artery intima-media thickness (IMT) was found to be a reliable and valid marker of CVD. We analyzed the relationship between IMT and clinical contributors including demographic and metabolic variables and an inflammatory marker, C-reactive protein (CRP). Methods: As a part of our ongoing prospective study of job stress on CVD, a group of 88 non-hypertensive (BP < 140/90 mm Hg), clinically healthy young professionals (average 33 years old) were analyzed. Common carotid artery IMT was measured by ultrasonography (HP Sono 5500) and analyzed with IôDP software. Multivariable linear regression was used to analyze the association between IMT and demographic factors (age, gender, ethnicity, work shift, smoking history, waist circumference), metabolic modulators (fasting glucose, HDL, LDL, and non-HDL levels) and an inflammatory marker (CRP). Results: We found that IMT was significantly associated with smoking history, age, ethnicity, LDL, fasting glucose and CRP levels. After adjusting for all of these demographic and metabolic factors, the inflammatory marker CRP level remained significantly positively associated with IMT. Summary: Our results suggest that both traditional risk factors including smoking, age, ethnicity, hypercholesterolemia and insulin resistance as well as the newly proposed systemic inflammation contribute to the early development of CVD. The sub-clinical inflammatory marker CRP is an independent risk factor of CVD in the apparently healthy, non-hypertensive young professionals.